High prevalence of noroviruses among hospitalized diarrheal patients in Bangladesh, 2011 - Shamsun Nahar; Mokibul Hassan Afrad; Noorjahan Begum; Feroz Al-Mamun; Azadul Kabir Sarker; Sumon Kumar Das; Abu SG Faruque; Mahmoud Reza Pourkarim; Mohammad Shabuddin Kabir Choudhuri; Tasnim Azim; Mustafizur Rahman (Journal of Infection in Developing Countries)
Introduction: Norovirus is not usually investigated in diarrheal patients in Bangladesh which may account for the many cases where no pathogens are identified. Methodology: Stool specimens collected from diarrheal patients from three hospitals in Bangladesh during 2011 were investigated for norovirus RNA using real-time RT-PCR assay with norovirus type specific primers and probes. Results: Of the 257 stool specimens tested, 28.4 % were norovirus positive. GII (71.2%) was the predominant strain followed by GI (20.5%), GI+GII (6.8%) and GIV (1.4%). Half of the norovirus positive stools (n=37) were co-infected with other pathogens. Conclusion: Continued surveillance of norovirus together with other viral and bacterial pathogens in hospitalized gastroenteritis patients as well as in the community will further elucidate the role and burden of different pathogens in diarrheal diseases.